Pengaruh Media Sosial Terhadap Perkembangan Bahasa Remaja - Sri Istanti, Reni; Jerni, Jerni; Rahma Sarfika, Siti; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrac: This study examines the influence of social media on the language development of adolescents. Utilizing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving adolescent social media users. The results indicate that social media has a significant impact on adolescent language, including vocabulary enrichment, the emergence of new slang, and the tendency to use informal language in daily communication. However, excessive use of non-standard language can reduce proficiency in formal Indonesian and lead to misunderstandings. The findings highlight the need for guidance in the use of language on social media to maintain the quality and identity of the Indonesian language among adolescents.